An 18-mo randomized, double-blind, placebo-controlled trial of DHA-rich fish oil to prevent age-related cognitive decline in cognitively normal older adults. Issue 5 (20th April 2018) - Danthiir, Vanessa; Hosking, Diane E; Nettelbeck, Ted; Vincent, Andrew D; Wilson, Carlene; O'Callaghan, Nathan; Calvaresi, Eva; Clifton, Peter; Wittert, Gary A
ABSTRACT: Background: Fish oil trials in cognitively healthy older adults have yielded inconsistent results. Supplementation may differentially affect the domains that underpin cognitive performance, and effects may differ across sex or genotype. Objective: The aim of this study was to test whether docosahexaenoic acid (DHA)–rich fish oil slows 18-mo cognitive decline in cognitively healthy elders. Design: In a double-blind, randomized, placebo-controlled, parallel-group trial, cognitively healthy Australian community-dwelling adults (aged 65–90 y) consumed either 1720 mg DHA and 600 mg eicosapentaenoic acid or low-polyphenolic olive oil daily, as capsules, for 18 mo. Groups were allocated by permuted-block randomization and stratified by age. Cognitive assessment was conducted at baseline and then every 6 mo. Primary analyses tested the difference between groups in the rate of 18-mo cognitive change via latent growth curve models on any of the following: reasoning, working memory, short-term memory, retrieval fluency, and cognitive speed-related constructs. Treatment interactions with sex and APOE-ε4 were tested. Secondary outcomes were self-reported changes in well-being and everyday functioning, blood pressure, biomarkers of n–3 (ω-3) long-chain polyunsaturated fatty acids (LC PUFAs), lipids, glucose metabolism, inflammation, oxidative stress, DNA damage, and Mini-Mental State Examination. Results: A total of 403 people were randomly assigned. Data from those who completed baseline were analyzed ( n  = 390; intervention n  = 194, control n  = 196). Daily supplementation with 2.3 g DHA-rich fish oil for 18 mo did not maintain or improve cognitive performance. A small negative main effect was found on psychomotor speed (intervention = –0.02, 95% CI: –0.04 to 0.00; d  = 0.24, P  = 0.03). Treatment effects differed according to sex on retrieval fluency and some speed-based domains, including psychomotor speed, and according to APOE-ε4 carrier status on reaction time and reasoning. For secondary outcomes, treatment was associated with increased perceived cognitive mistakes ( d  = 0.24; P  = 0.003), increased oxidative stress, and expected changes in fatty acid metabolism. Conclusions: Findings do not support supplementing older adults with fish oil to prevent cognitive decline. Treatment interactions with sex and APOE-ε4 carrier status warrant further investigation. This trial was registered at the Australia and New Zealand Clinical Trials Register (ANZCTR) as ACTRN12607000278437.